EP193/#340 Remote gynecologic oncology perioperative care through mobile application: a prospective cohort study to assess feasibility and patient engagement. (4th December 2022) - Kim, Soyoun Rachel; Laframboise, Stephane; Manhertz, Jodi-Ann; Bernardini, Marcus; Ferguson, Sarah; May, Taymaa; Hogen, Liat; Cybulska, Paulina; Bouchard-Fortier, Genevieve
Abstract : Objectives: Mobile applications (apps) may increase patient-provider interactions in the perioperative setting and reduce preventable complications. We conducted a prospective cohort study to evaluate the feasibility and patient engagement for a comprehensive mobile app designed for remote gynecologic oncology perioperative care. Methods: We designed a mobile app for those undergoing minimally invasive hysterectomy at a tertiary cancer center. Patients had access to the app from their initial consultation up to 30 days after their surgery. The app sent out instructions in the pre- and post-operative setting, provided educational videos, sent out daily queries about postoperative symptoms, and allowed patients to initiate text messages or video calls during their recovery. All patients completed a survey at enrollment and at 30-day follow-up. Results: Of 37 patients who were approached, 24 (65%) participated and 17 (71%) have fully completed the pathway with 7 (29%) still in the process of completing their perioperative journey. The median age at enrolment was 65 (50–84). Participant engagement and compliance was high (75%), as measured by the response rate to the daily queries and completion of surveys. Of those who completed the survey, 100% would recommend the app to other patients, and found that the app improved their engagement with their care providers. All participants found that the educational components were helpful for their recovery at home. Overall, 91% were satisfied with the remote monitoring process and 91% felt empowered through use of the app. Conclusions: Mobile app in perioperative care of gynecology oncology patients is well accepted and feasible.